Pengaruh Kepuasan Konsumen SPBU melalui Digitalisasi dan Kualitas Pelayanan - Nirwana, Ida; Yeni, Afni; Abdul Hijrah, Tedi (Jurnal Manajemen Dirgantara, 2024)
This study aims to determine the effect of gas station digitalization and service quality on customer satisfaction. Primary data were taken from respondents of gas station 13,264,518 Koto Gadang Guguk, Solok Regency. The type of research used is quantitative descriptive research. The results of the study indicate that gas station digitalization has an effect on customer satisfaction with a t-value of 5.522 (i.e. > 1.98761) and a significant probability value of 0.000 (i.e. <0.05). Service quality also has an effect on customer satisfaction with a t-value of 3.063 and a significant probability value of 0.003. The gas station digitalization variable and the service quality variable simultaneously have an effect on customer satisfaction with a coefficient of determination (R2) of 0.529 or 52.9%, while the remaining 47.1% is influenced by other variables not examined in this study such as motivation, leadership, workload and others.